Ca2+ mediates extracellular vesicle biogenesis through alternate pathways in malignancy. Issue 1 (3rd March 2020) - Taylor, Jack; Azimi, Iman; Monteith, Gregory; Bebawy, Mary
ABSTRACT: Extracellular vesicles (EVs) are small membrane vesicles that serve as important intercellular signalling intermediaries in both malignant and non‐malignant cells. For EVs formed by the plasma membrane, their biogenesis is characterized by an increase in intracellular calcium followed by successive membrane and cytoskeletal changes. EV‐production is significantly higher in malignant cells relative to non‐malignant cells and previous work suggests this is dependent on increased calcium mobilization and activity of calpain. However, calcium‐signalling pathways involved in malignant and non‐malignant EV biogenesis remain unexplored. Here we demonstrate; malignant cells have high basal production of plasma membrane EVs compared to non‐malignant cells and this is driven by a calcium–calpain dependent pathway. Resting vesiculation in malignant cells occurs via mobilization of calcium from endoplasmic reticulum (ER) stores rather than from the activity of plasma membrane calcium channels. In the event of ER store depletion however, the store‐operated calcium entry (SOCE) pathway is activated to restore ER calcium stores. Depleting both ER calcium stores and blocking SOCE, inhibits EV biogenesis. In contrast, calcium signalling pathways are not activated in resting non‐malignant cells. Consequently, these cells are relatively low vesiculators in the resting state. Following cellular activation however, an increase in cytosolic calcium and activation of calpain increase in EV biogenesis. These findings contribute to furthering our understanding of extracellular vesicle biogenesis. As EVs are key mediators in the intercellular transfer of deleterious cancer traits such as cancer multidrug resistance (MDR), understanding the molecular mechanisms governing their biogenesis in cancer is the crucial first step in finding novel therapeutic targets that circumvent EV‐mediated MDR.